The Power-Sharing System of DFIG-Based Shaft Generator Connected to a Grid of the Ship - Trong-Thang Nguyen (IEEE Access, 2021)
This article proposes a control system for a ship power station using a doubly-fed-induction generator (DFIG). Firstly, the author analyzes the characteristics of the power generation system using DFIG based on the rotor sync signal technique and then proposes a control system for adjusting the active and reactive power of the generator supplied to the grid. The advantage of the rotor sync technique is that two control channels of active and reactive power are independent. It is favorable for the author proposes the Fuzzy-PID controller for each control channel. The result is that active and reactive power always follow the desired values in a fast response time. Thus, the author applies this proposed system for automatic load division in a parallel power grid on the ship. The entire generator system has well ensured the load distribution between the shaft-generator and the grid in the case of changes in load consumption and rotor speed of the generator.